ANALISIS FAKTOR PENYEBAB DOMINAN KEJADIAN RUPTURE PERINEUM PADA PERSALINAN SPONTAN DI RSD KALISAT JEMBER - Agustin, Maudy (Poltekkes Kemenkes Malang, 2023)
Perineal rupture is a labor problem which is one of the biggest causes of maternal death. A preliminary study conducted at the Kalisat Hospital, Jember in January until May 2022, found that from a total of 510 mothers who gave birth spontaneously, 316 women experienced perineal rupture. This study aims to analyze the dominant factors causing perineal rupture in spontaneous labor, among others, related to maternal variables parity, birth spacing, maternal age, Helper how to lead pushing, pushing position, episiotomy, Fetus presentation of deflection, breech position, dystocia). shoulder, fetal weight interpretation. This study used a quantitative method with a cross-sectional approach. The population of this study was 297 and 100 mothers had perineal rupture. The sampling technique used was Accidental Sampling. This data was collected using observation sheets (screening sheets, partograph sheets, and checklist sheets) and analyzed using univariate and bivariate analysis methods with the Odds Ratio test in the SPSS 21 program. the incidence of perineal rupture from the three dominant factors, namely maternal, surrogate, and fetal each was 0.000 with a probability of 6.96 times for gestational spacing, episiotomy was 0.006 with a probability of 5.45 times, and breech position 0.001 with a chance of 5.96 times. Thus, the conclution that the dominant factor causing perineal rupture in the delivery room at Kalisat Hospital was distance between pregnancies. For this reason, it is necessary to make efforts to prevent the incidence of perineal rupture, such as the implementation of classes for pregnant women which can cover all preparations of mothers in going through the delivery process.